The Relational Constitution of Institutional Spaces. Balancing Act between Openness and Pedagogical Space Shaping in Open Child and Youth Work - Christian Reutlinger (Social Work and Society)
This article examines the tension between openness and processes of institutionalization in the German social work field of open child and youth work (German: Offene Kinder- und Jugendarbeit). Drawing on a case study, the article first illustrates how youth workers, by adopting the principle of openness enshrouded in the concept of open child and youth work, were able to successfully develop a youth center as an institute for social work. In its initial phase, as this article describes, openness helped the youth center achieve a boom in youth participation. From a spatial perspective, the article depicts that this period of success was, however, followed by a challenging lull, which resulted from processes of exclusion as the youth center was perceived to be a closed space for particular youth groups. Paradoxically, therefore, this lull was the converse of the youth workers' previous success in opening the center to"their" young people. In opening the center to a particular community of young people, the youth workers implicitly closed the center to others. The third section therefore reflects on the youth workers' processes of openness and exclusion: How can youth workers successfully navigate the everyday"jungle" of their work with their particular youth group without excluding other young people? Is it even possible to adopt an open approach to social work without excluding some groups? The article concludes with conceptual reflections on how social work institutions can be understood as institutional spaces and how they can be spatially decoded and professionally constructed. Accordingly, it shows how, on the one hand, youth workers' institutional practices are shaped by both the spatial environment (cf. Gutheil, 1992; Germain, 1981; Weinstein, 1979; Zapf, 2010) and institutional structures (cf. Goffman, 1961; Göhlich, 2010; McDonald, 2006; Foucault, 1977). On the other hand, the article explores how youth workers think and act always impact the institution and its programs (Barley/Tolbert, 1997) uncovering how professionals construct the available space and significantly influence the social relations and systems that are developed within its spatiality (DeVerteuil/Wilton, 2009).